High-voltage-resistant polymer-based electrolyte membrane as well as preparation method and application thereof
By preparing high voltage resistant polymer-based electrolyte membrane, the problem of poor circulation stability of polymer solid electrolyte matching ternary positive electrode materials at high voltage is solved, and the energy density of lithium batteries is improved and long circulation stability is achieved, especially with high The voltage nickel cobalt manganese positive electrode shows good battery performance after assembly.
Patent Information
- Application Number
- CN202411296679.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-09-18
- Publication Date
- 2025-01-03
- Estimated Expiration
- 2044-09-18
AI Technical Summary
The existing polymer solid electrolytes have poor cycle stability matching ternary positive electrode materials at high voltages, making it difficult to effectively improve the energy density of lithium batteries.
Using a high voltage resistant polymer-based electrolyte film, the polymer, lithium salt and high voltage additive lithium difluorophosphate are dissolved in an organic solvent, and the film is formed after adding plasticizer to match high voltage nickel. Cobalt-manganese ternary cathode material improves electrochemical window and cycle stability.
Achieve high energy density and long cycle stability, ensuring the battery performance of solid-state batteries under high voltage conditions, especially the charging curve and discharge curve of the battery assembled with high voltage positive electrode ternary nickel cobalt manganese after 100 turns. .
Smart Images

Figure CN119253045A_ABST
Abstract
Description
Technical Field
[0001] The present invention belongs to the technical field of battery materials, and in particular relates to a high-voltage resistant polymer-based electrolyte membrane and a preparation method and application thereof. Background Art
[0002] Liquid lithium batteries have been widely used in 3C, power batteries, energy storage and other fields. Solid-state batteries use non-flammable and non-volatile solid electrolytes to replace flammable organic liquid ester electrolytes, which can improve the safety of the battery system, while better adapting to high-energy positive and negative electrodes and reducing the weight of the system to achieve increased energy density. Increasing the operating voltage range of lithium batteries is one of the important ways to increase battery energy density. For solid-state batteries, solid electrolytes need to have good compatibility with lithium metal while matching high-voltage positive electrode materials and having high voltage resistance.
[0003] At present, solid electrolytes mainly include two categories: inorganic solid electrolytes and polymer solid electrolytes. Inorganic solid electrolytes mainly include oxides and sulfides. The ionic conductivity of oxide materials is relatively low, and the interface impedance between the positive and negative electrodes is large; the preparation conditions of sulfide materials are relatively harsh, and industrialization is more difficult. Polymer solid electrolytes have the advantages of good thermal stability, high stability to lithium, good cycle performance, and can be prepared into flexible thin-film batteries. They are currently the easiest direction for industrialization. However, the polymer solid electrolytes currently under research still generally have the problem of not being able to withstand high voltages, resulting in poor cycle stability when matching ternary positive electrode materials, making it difficult to effectively improve the energy density of the battery. Summary of the invention
[0004] In view of the shortcomings of the prior art, the present invention provides a high-voltage resistant polymer-based electrolyte membrane and a preparation method and application thereof. The prepared high-voltage resistant polymer-based electrolyte membrane has a higher oxidation electrochemical window, and matching with a high-voltage nickel-cobalt-manganese ternary positive electrode material can improve the energy density of the solid-state battery. The obtained solid-state battery has good long-cycle stability.
[0005] In order to achieve the above object, the technical solution adopted by the present invention is as follows:
[0006] A method for preparing a high voltage resistant polymer-based electrolyte membrane comprises the following steps:
[0007] Step S1, dissolving the polymer and lithium salt in an organic solvent to prepare a uniform solution;
[0008] Step S2, adding lithium difluorophosphate, a high voltage additive, to the solution obtained in step S1 and stirring evenly;
[0009] Step S3, adding a plasticizer additive to the solution obtained in step S2, stirring evenly, then casting the solution into a film or coating it on a diaphragm, and drying it to obtain a high voltage resistant polymer-based electrolyte membrane.
[0010] Furthermore, in step S1, the polymer is selected from one or more of polyethylene oxide, polypropylene oxide, polyvinylidene fluoride, polyacrylonitrile, polyvinylidene fluoride-hexafluoropropylene, polymethyl methacrylate, and polycaprolactone.
[0011] Furthermore, in step S1, the lithium salt is selected from one or more of lithium bis(trifluoromethylsulfonyl)imide, lithium perchlorate, and lithium bis(trifluoromethylsulfonyl)imide.
[0012] Furthermore, in step S1, the organic solvent is selected from one or more of acetonitrile, N,N-dimethylformamide, N-methylpyrrolidone, acetone, tetrahydrofuran, propylene carbonate, dimethyl carbonate, ethyl methyl carbonate, and diethyl carbonate.
[0013] Furthermore, in step S2, the mass of the high voltage additive accounts for 1% to 8% of the mass of the polymer.
[0014] Furthermore, in step S3, the plasticizer is selected from one or more of ethylene carbonate, trimethyl phosphite, succinonitrile, suberonitrile, and polycarbonate.
[0015] The present invention also provides a high voltage resistant polymer-based electrolyte membrane, which is prepared by the above-mentioned preparation method of the high voltage resistant polymer-based electrolyte membrane.
[0016] The present invention also provides an application of a high voltage resistant polymer-based electrolyte membrane in a solid-state battery, and a solid-state battery is prepared by matching the high voltage resistant polymer-based electrolyte membrane with a high voltage positive electrode active material and a negative electrode material.
[0017] Furthermore, the high voltage positive electrode active material is ternary nickel-cobalt-manganese.
[0018] Furthermore, the negative electrode material is a lithium sheet.
[0019] Beneficial Effects
[0020] The existing polymer-based electrolytes have a narrow electrochemical window, which makes it difficult to match high-voltage positive electrodes. The high-voltage-resistant polymer-based electrolyte membrane prepared by the present invention has a higher electrochemical window, can match high-voltage positive electrodes, and effectively improve the energy density of solid-state batteries. At the same time, the solid-state battery assembled by matching the prepared high-voltage-resistant polymer-based electrolyte membrane with the high-voltage positive electrode ternary nickel-cobalt-manganese (NCM111) maintains basically stable voltage platforms of the charging curve and the discharging curve after 100 cycles, showing good long-cycle performance. BRIEF DESCRIPTION OF THE DRAWINGS
[0021] Figure 1 LSV test curves of polymer-based electrolyte membranes prepared in Examples and Comparative Examples;
[0022] Figure 2 A long cycle performance test diagram of a solid-state battery assembled by matching the polymer-based electrolyte membrane prepared in Example 1 and Example 2 with a high-voltage positive electrode ternary nickel-cobalt-manganese (NCM111);
[0023] Figure 3 The long cycle performance test diagram of the solid-state battery assembled by matching the polymer-based electrolyte membrane prepared in Example 3 and Comparative Example 1 with the high-voltage positive electrode ternary nickel-cobalt-manganese (NCM111);
[0024] Figure 4 The charge and discharge curves of the solid-state battery assembled by matching the polymer-based electrolyte membrane prepared in Example 3 with the high-voltage positive electrode ternary nickel-cobalt-manganese (NCM111);
[0025] Figure 5 The charge and discharge curves of the solid-state battery assembled by matching the polymer-based electrolyte membrane prepared in Comparative Example 1 with the high-voltage positive electrode ternary nickel-cobalt-manganese (NCM111). DETAILED DESCRIPTION
[0026] The present invention is further illustrated by specific examples below. These examples are exemplary and are intended to illustrate the problem and explain the present invention, but are not intended to be limiting.
[0027] Example 1
[0028] A method for preparing a high voltage resistant polymer-based electrolyte comprises the following steps:
[0029] Step S1, dissolving 1 g of polyethylene oxide (PEO) and 0.362 g of lithium bis(trifluoromethylsulfonyl)imide (LiTFSI) in acetonitrile, and heating at 60° C. to dissolve;
[0030] Step S2, adding 0.01 g of lithium difluorophosphate (LiOP2F2) to the solution obtained in step S1 and stirring for 1 h;
[0031] Step S3, adding 0.1 g of ethylene carbonate (EC) to the solution obtained in step S2, stirring for 12 hours, casting the mixed solution on a polytetrafluoroethylene plate to form a film, heating and drying by air blowing, and obtaining a high-voltage resistant polymer-based electrolyte membrane.
[0032] Example 2
[0033] A method for preparing a high voltage resistant polymer-based electrolyte comprises the following steps:
[0034] Step S1, dissolving 1 g of polyethylene oxide (PEO) and 0.362 g of lithium bis(trifluoromethylsulfonyl)imide (LiTFSI) in acetonitrile, and heating at 60° C. to dissolve;
[0035] Step S2, adding 0.04 g of lithium difluorophosphate (LiOP2F2) to the solution obtained in step S1 and stirring for 1 h;
[0036] Step S3, adding 0.1 g of ethylene carbonate (EC) to the solution obtained in step S2, stirring for 12 hours, casting the mixed solution on a polytetrafluoroethylene plate to form a film, heating and drying by air blowing, and obtaining a high-voltage resistant polymer-based electrolyte membrane.
[0037] Example 3
[0038] A method for preparing a high voltage resistant polymer-based electrolyte comprises the following steps:
[0039] Step S1, dissolving 1 g of polyethylene oxide (PEO) and 0.362 g of lithium bis(trifluoromethylsulfonyl)imide (LiTFSI) in acetonitrile, and heating at 60° C. to dissolve;
[0040] Step S2, adding 0.08 g of lithium difluorophosphate (LiOP2F2) to the solution obtained in step S1 and stirring for 1 h;
[0041] Step S3, adding 0.1 g of ethylene carbonate (EC) to the solution obtained in step S2, stirring for 12 hours, casting the mixed solution on a polytetrafluoroethylene plate to form a film, heating and drying by air blowing, and obtaining a high-voltage resistant polymer-based electrolyte membrane.
[0042] Comparative Example 1
[0043] A method for preparing a non-high voltage resistant polymer-based electrolyte comprises the following steps:
[0044] 1 g of polyethylene oxide (PEO) and 0.362 g of lithium bis(trifluoromethylsulfonyl)imide (LiTFSI) were dissolved in acetonitrile, heated at 60°C for dissolution, stirred for 12 h, and the mixed solution was poured onto a polytetrafluoroethylene plate to form a film, heated and dried by air blowing to obtain a non-high-voltage-resistant polymer-based electrolyte membrane.
[0045] Linear Sweep Voltammetry (LSV) Test
[0046] Figure 1The results of the linear sweep voltammetry (LSV) test experiment of the polymer-based electrolyte membrane prepared by the above-mentioned embodiments and comparative examples. The polymer-based electrolyte membrane prepared in comparative example 1 does not add the high-voltage additive lithium difluorophosphate (LiOP2F2), and the polymer-based electrolyte membranes prepared in Examples 1, 2 and 3 add different proportions of high-voltage additive lithium difluorophosphate (LiOP2F2). The oxidation electrochemical window of the polymer-based electrolyte membrane prepared in comparative example 1 is 3.6V, and the oxidation electrochemical windows of the polymer-based electrolyte membranes prepared in Examples 1, 2 and 3 are all higher than 4V, wherein the oxidation electrochemical window of the polymer-based electrolyte membrane prepared in Example 3 is 4.8V, indicating that after adding lithium difluorophosphate (LiOP2F2), the high-voltage resistance of the polymer-based electrolyte membrane is greatly improved. With the increase in the dosage of the high-voltage additive lithium difluorophosphate (LiOP2F2), the oxidation electrochemical window of the polymer-based electrolyte membrane is also steadily increasing, further indicating that lithium difluorophosphate (LiOP2F2) plays a key role in improving the high-voltage resistance of the polymer-based electrolyte membrane.
[0047] Long cycle performance test experiment of assembled solid-state battery
[0048] The polymer-based electrolyte membranes prepared in Example 1, Example 2, Example 3 and Comparative Example 1 were assembled into CR2023 button batteries to test the electrochemical performance. The positive electrode active material was ternary nickel cobalt manganese (NCM111), and the positive electrode active material loading was about 2.0 mg / cm 2 The negative electrode is a lithium sheet. The battery is placed in an oven at 60°C for 8 hours before testing. The test voltage range is 2.7-4.2V, and the test rate is 0.2C (1C = 160mA / g).
[0049] Figure 2 The long cycle performance test result diagram of the solid-state battery assembled by matching the polymer-based electrolyte membrane prepared in Example 1 and Example 2 with the high-voltage positive electrode ternary nickel-cobalt-manganese (NCM111) is shown in FIG. Figure 3 The long cycle performance test results of the solid-state battery assembled by matching the polymer-based electrolyte membrane prepared in Example 3 and Comparative Example 1 with the high-voltage positive electrode ternary nickel-cobalt-manganese (NCM111). Compared with the long cycle stability of the CR2023 button battery assembled with the polymer-based electrolyte membrane prepared in Comparative Example 1, the polymer-based electrolyte membranes prepared in Examples 1, 2 and 3 assembled with the CR2023 button battery showed better long cycle stability.
[0050] Table 1 shows the capacity retention results of CR2023 type button batteries assembled with the polymer-based electrolyte membranes prepared in Example 1, Example 2, Example 3 and Comparative Example 1 after 100 cycles. After 100 cycles, the discharge specific capacity of the CR2023 button battery assembled with the polymer-based electrolyte membrane prepared in Comparative Example 1 was significantly reduced, and the capacity retention rate was 4.8%. After 100 cycles, the discharge specific capacity of the CR2023 button battery assembled with the polymer-based electrolyte membrane prepared by adding different proportions of the high-voltage additive lithium difluorophosphate (LiOP2F2) did not show a significant change compared with the first-cycle discharge specific capacity, and the capacity retention rate was higher than 75%, showing good long-cycle stability. Among them, the capacity retention rate of the CR2023 button battery assembled with the polymer-based electrolyte membrane prepared by adding the highest dose of the high-voltage additive lithium difluorophosphate (LiOP2F2) was 91.7% after 100 cycles, showing the best long-cycle stability. Therefore, lithium difluorophosphate (LiOP2F2) plays a key role in improving the long-cycle stability of solid-state batteries assembled with polymer-based electrolyte membranes.
[0051] Table 1 Discharge capacity data of the first cycle and after 100 cycles
[0052]
[0053]
[0054] Charge and discharge curve test experiment of assembled solid-state battery
[0055] Figure 4 The charge and discharge curves of the solid-state battery assembled by matching the polymer-based electrolyte membrane prepared in Example 3 with the high-voltage positive electrode ternary nickel-cobalt-manganese (NCM111) are shown in FIG. Figure 5 The charge and discharge curves of the solid-state battery assembled by matching the polymer-based electrolyte membrane prepared in Comparative Example 1 with the high-voltage positive electrode ternary nickel-cobalt-manganese (NCM111). After 100 cycles of the solid-state battery assembled by matching the polymer-based electrolyte membrane prepared in Example 3 with the high-voltage positive electrode ternary nickel-cobalt-manganese (NCM111), the voltage platform of the charge curve and the discharge curve remained basically stable, and the curve shape did not change significantly, which was consistent with the good long cycle performance of the battery. After 50 cycles of the solid-state battery assembled by matching the polymer-based electrolyte membrane prepared in Comparative Example 1 with the high-voltage positive electrode ternary nickel-cobalt-manganese (NCM111), the shape characteristics of the charge curve and the discharge curve changed significantly, showing a significantly increased polarization potential and a sharply reduced reversible specific capacity. Therefore, lithium difluorophosphate (LiOP2F2) plays a key role in maintaining the steady state of the charge and discharge curves of the solid-state battery assembled by the polymer-based electrolyte membrane.
Claims
1. A method for preparing a high voltage resistant polymer-based electrolyte membrane, characterized in that: The steps include: Step S1, dissolving the polymer and lithium salt in an organic solvent to prepare a uniform solution; Step S2, adding lithium difluorophosphate, a high voltage additive, to the solution obtained in step S1 and stirring evenly; Step S3, adding a plasticizer additive to the solution obtained in step S2, stirring evenly, then casting the solution into a film or coating it on a diaphragm, and drying it to obtain a high voltage resistant polymer-based electrolyte membrane.
2. The method for preparing a high voltage resistant polymer-based electrolyte membrane according to claim 1, characterized in that: In step S1, the polymer is selected from one or more of polyethylene oxide, polypropylene oxide, polyvinylidene fluoride, polyacrylonitrile, polyvinylidene fluoride-hexafluoropropylene, polymethyl methacrylate, and polycaprolactone.
3. The method for preparing a high voltage resistant polymer-based electrolyte membrane according to claim 1, characterized in that: In step S1, the lithium salt is selected from one or more of lithium bis(trifluoromethylsulfonyl)imide, lithium perchlorate, and lithium bis(trifluoromethylsulfonyl)imide.
4. The method for preparing a high voltage resistant polymer-based electrolyte membrane according to claim 1, characterized in that: In step S1, the organic solvent is selected from one or more of acetonitrile, N,N-dimethylformamide, N-methylpyrrolidone, acetone, tetrahydrofuran, propylene carbonate, dimethyl carbonate, ethyl methyl carbonate, and diethyl carbonate.
5. The method for preparing a high voltage resistant polymer-based electrolyte membrane according to claim 1, characterized in that: In step S2, the mass of the high voltage additive accounts for 1% to 8% of the mass of the polymer.
6. The method for preparing a high voltage resistant polymer-based electrolyte membrane according to claim 1, characterized in that: In step S3, the plasticizer is selected from one or more of ethylene carbonate, trimethyl phosphite, succinonitrile, suberonitrile, and polycarbonate.
7. A high voltage resistant polymer-based electrolyte membrane, characterized in that: The high voltage resistant polymer-based electrolyte membrane is prepared by the preparation method of any one of claims 1 to 6.
8. Application of a high voltage resistant polymer-based electrolyte membrane in a solid-state battery, characterized in that: The solid-state battery is prepared by using the high-voltage-resistant polymer-based electrolyte membrane described in claim 7 to match high-voltage positive electrode active materials and negative electrode materials.
9. The use of the high voltage resistant polymer-based electrolyte membrane in a solid-state battery according to claim 8, characterized in that: The high voltage positive electrode active material is ternary nickel, cobalt and manganese.
10. The use of the high voltage resistant polymer-based electrolyte membrane in a solid-state battery according to claim 8, characterized in that: The negative electrode material is a lithium sheet.
Citation Information
Patent Citations
Solid-state battery capable of operating at room temperature and preparation method thereof
CN110429325A
Nitride-reinforced polymer electrolyte, preparation method and long-life solid-state lithium ion battery
CN110994017A
Gel polymer lithium ion electrolyte and battery containing electrolyte
CN115832422A
Solid electrolyte, preparation method of positive electrode coated with solid electrolyte, and lithium battery
CN115986204A
Polymer-based modifying interlayer for lithium anode and solid electrolyte interface and method of preparing the same
WO2024097083A1
Cited By
High-voltage-resistant cross-linked polymer solid electrolyte and preparation method thereof
CN121172232A
